Evaluating Carbon Offsets from Forestry and Energy Projects : How Do They Compare? - Chomitz, Kenneth M. (World Bank, Washington, DC, 2014)
Under the Kyoto Protocol, industrial countries accept caps on their emissions of greenhouse gases. They are permitted to acquire offsetting emissions reductions from developing countries - which do not have emissions limitations - to assist in complying with these caps. Because these emissions reductions are defined against a hypothetical baseline, practical issues arise in ensuring that the reductions are genuine. Forestry-related emissions reduction projects are often thought to present greater difficulties in measurement and implementation, than energy-related emissions reduction projects. The author discusses how project characteristics affect the process for determining compliance with each of the criteria for qualifying. Those criteria are: 1) Additionality. Would these emissions reductions not have taken place without the project? 2) Baseline and systems boundaries (leakage). What would business-as-usual emissions have been without the project? And in this comparison, how broad should spatial, and temporal system boundaries be? 3) Measurement (or sequestration). How accurately can we measure actual with-project emissions levels? 4) Duration or permanence. Will the project have an enduring mitigating effect? 5) Local impact. Will the project benefit its neighbors? For all the criteria except permanence, it is difficult to find generic distinctions between land use change and forestry and energy projects, since both categories comprise diverse project types. The important distinctions among projects have to do with such things as: a) The level and distribution of the project's direct financial benefits. b) How much the project is integrated with the larger system. c) The project components' internal homogeneity and geographic dispersion. d) The local replicability of project technologies. Permanence is an issue specific to land use and forestry projects. The author describes various approaches to ensure permanence, or adjust credits for duration: the ton-year approach (focusing on the benefits from deferring climatic damage, and rewarding longer deferral); the combination approach (bundling current land use change and forestry emissions reductions with future reductions in the buyer's allowed amount); a technology-acceleration approach; and an insurance approach.